Does domestic offshoring precede international offshoring? Industry-level evidence - Franz-Josef Bade; Eckhardt Bode; Eleonora Cutrini (Kiel Institute for the World Economy (IfW), 2011)
This paper presents descriptive evidence suggesting that there may be something to be learned about the future patterns of international offshoring from the recent patterns of 'domestic offshoring', the relocation of activities across regions within countries. Industries appear to offshore activities first within the same country and only later across the national border. Investigating the domestic and international offshoring patterns for West German manufacturing industries between 1992 and 2007, we find that, on the one hand, industries that offshored more extensively domestically offshored less extensively internationally, and vice versa. On the other hand, we find that those industries that offshored more extensively domestically were still in earlier stages of their life cycles while those that offshored more extensively internationally were already in later stages. International unbundling may consequently not be as unpredictable as it is currently believed to be.
Keywords: C46; F21; R12; 330; International offshoring; domestic offshoring; functional fragmentation; industry life cycle; Germany; K density; Offshoring; International; Verarbeitendes Gewerbe; Lebenszyklus; Outsourcing; Standortwahl; Deutschland